Hediste Malmgren 1867 - Salazar-Vallejo, Sergio I.; León-González, Jesús Angel De; Conde-Vela, Víctor M. (Zenodo, 2021)
Key to species of Hediste Malmgren, 1867 1. Areas VII–VIII with a single row of denticles (rarely 2–5 supernumerary paragnaths).2 – Areas VII–VIII with two rows of denticles; palpophores continuous, 3–4 × as long as wide; area II with about 15 paragnaths per side.7 2. Palpophores with a transverse depression (looking bisegmented); longest tentacular cirri reaching chaetigers 2–3; area II with about 15 medium-sized paragnaths per side . . H. limnicola (Johnson, 1903) (California) – Palpophores continuous, 2 × as long as wide.3 3. Area II with 10 or fewer large paragnaths per side; longest tentacular cirri reaching chaetigers 6–9; areas VII–VIII with 19–26 paragnaths . H. japonica (Izuka, 1908) (Japan) – Area II with more than 20 tiny paragnaths per side; longest tentacular cirri reaching chaetigers 8–9; areas VII–VIII with 9–35 paragnaths . H. atoka Sato & Nakashima, 2003 (Japan) – Area II with 10–20 paragnaths.4 4. Areas VII–VIII with 8 paragnaths; longest tentacular cirri reaching chaetiger 5 . . H. sakhalinensis (Okuda, 1935) (Sakhalin Island, Japan Sea) – Areas VII–VIII with 11–41 paragnaths.5 5. Posterior parapodia with median ligule as long as dorsal one; longest tentacular cirri reaching chaetigers 6–12 . H. diadroma Sato & Nakashima, 2003 (Japan) – Posterior parapodia with median ligule markedly smaller than dorsal one.6 6. Longest tentacular cirri reaching chaetiger 6 . H. lighti (Hartman, 1938) (California) – Longest tentacular cirri reaching chaetiger 2 . H. rabatensis (Mohammad, 1989) (Morocco) 7. Neuropodial anchylosed falcigers subdistally constricted; tentacular cirri reaching chaetigers 5–7 . H. diversicolor (Müller, 1776) sensu Hartmann-Schröder 1996 (Baltic Sea) – Neuropodial anchylosed falcigers subdistally swollen; tentacular cirri reaching chaetigers 5–9 . . H. diversicolor (Müller, 1776) sensu Khlebovich 1996 (Black Sea; matching N. falsa (de Quatrefages, 1866)) Remarks Smith (1959), after comparing the types, concluded that H. lighti was a junior synonym of H. limnicola . They ...